2006
DOI: 10.3748/wjg.v12.i48.7844
|View full text |Cite
|
Sign up to set email alerts
|

Depression in patients with irritable bowel syndrome in Jos, Nigeria

Abstract: IBS is significantly associated with major depression but not gender and bowel subtypes of the patients. Patients with IBS need to be evaluated for depression due to the highly significant relationship between the two conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 23 publications
2
23
0
2
Order By: Relevance
“…It was also shown in this study that there were more significant functioning disturbances among people with comorbid IBS and general anxiety disorder. In the current study, lifetime prevalence rates of anxiety and depressive disorders in the control group with GERD are similar to the prevalence rates obtained from epidemiological studies in the general population (anxiety disorders 30% vs. 25%, depressive disorders 16% vs. 16%;) [24][25][26], whereas in the group with IBS the prevalence rates ranged from 15% to 52% with respect to depressive disorders and from 22% to 44% with respect to anxiety disorders [13,[27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 80%
“…It was also shown in this study that there were more significant functioning disturbances among people with comorbid IBS and general anxiety disorder. In the current study, lifetime prevalence rates of anxiety and depressive disorders in the control group with GERD are similar to the prevalence rates obtained from epidemiological studies in the general population (anxiety disorders 30% vs. 25%, depressive disorders 16% vs. 16%;) [24][25][26], whereas in the group with IBS the prevalence rates ranged from 15% to 52% with respect to depressive disorders and from 22% to 44% with respect to anxiety disorders [13,[27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, previous urinary metabonomic analysis in a depressed animal model has shown that depressed behavior is associated with changes in gut microflora (17). Interestingly, several clinical studies have demonstrated that MDD patients display a high comorbidity of irritable bowel syndrome (IBS) (40,41), a disorder involving gut microflora. The fecal microflora in IBS patients show abnormally higher numbers of facultative organisms and lower numbers of lactobacilli and bifidobacteria (42).…”
Section: Fig 2 Metabonomic Analysis Of Urine Samples From Mdd Subjementioning
confidence: 99%
“…12 A number of studies have examined the prevalence of depression and anxiety in IBS. [13][14][15][16][17][18][19][20][21][22] Limitations of these studies include selection bias, disparate diagnostic criteria for IBS, depression and anxiety and assessing psychological traits as opposed to psychiatric diagnosis. Using a validated, well-characterized pharmacy reimbursement database and drug prescribing as a surrogate marker for psychological and IBS diagnosis, we examined the co-existence of psychological comorbidity in IBS in the community and evaluated the persistence of psychological co-morbidity over time.…”
Section: Introductionmentioning
confidence: 99%